EDM: surface characterization on machining tungsten carbide without and with vibration / Norliana Mohd Abbas … [et al.] - Mohd Abbas, Norliana; Solomon, Darius G.; Bahari, Md. Fuad; Abd. Shukor, Mohd. Hamdi; Prihandana, Gunawan Setia (2008)
One of the non-traditional machining methods is Electrical Discharge Machining (EDM). The process is based on removing material from a part by a series of repeated electrical discharges between tool called electrode and the work piece with the presence of dielectric. EDM with vibration is one of current research trends. It expand the application of EDM and able to improve the machining performance on difficult to machine materials. This paper presents the surface morphologies resulting from different machining methods, current settings and polarities for work piece surfaces using stereomicroscope and SEM. Cracks, pockmarks and globules are found on higher magnification of the machined surface while machining is conducted without vibration. However, with the introduction of vibration during the machining has reduced the appearance of cracks, pockmarks and globules. The machining was conducted with Sodick A30R EDM machine available in Department of Engineering Design and Manufacture, Faculty of Engineering, Universiti Malaya. The machining used tungsten carbide work piece, copper electrode and current settings of 10A and 8A under positive as well as negative polarities. The amplitude and frequency of vibration selected are 1µm and 400Hz respectively.